The Impact of Students Assessing the Level of Difficulty Test Item on Interest and Motivation in Learning Mathematics - Rukli Rukli; Ma'rup Ma'rup (RIRAI Publisher, 2022)
According to Item Response Theory, the difficulty level is a characteristic of the test item. The difficulty level of the test items is a characteristic of the test items that are on a scale with the ability level parameter. However, this relationship has not been studied optimally, especially in students' interest and motivation in learning mathematics. This study examines the impact of student involvement in assessing the level of the difficulty test item on interest and motivation in learning mathematics with the approach of assessment as learning. The study involved 176 students from grade VII in SMP and MTs. High-level reasoning test items were adapted from TIMSS test items, while the interest and motivation instruments used a questionnaire. Data analysis used percentages and paired t test. The results showed the difference between before and after estimating the difficulty level test items to students' interest and motivation in learning mathematics. The interest and motivation of students in learning mathematics increased after estimating the level of difficulty of the test items. Therefore, to increase students' interest and motivation in learning mathematics, teachers can involve students in assessing the level of difficulty of the test items using the approach of assessment as learning.